2003
DOI: 10.1002/jbm.b.10020
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin contamination in wound dressings made of natural biomaterials

Abstract: Contamination by endotoxin of nine kinds of wound dressings made of natural biomaterials (calcium alginate, collagen, chitin, and poly-L-leucine) was examined with the use of water extracts. By applying the Limulus amoebocyte lysate (LAL) test, high concentrations of endotoxin were detected in extracts from three kinds of products made of calcium alginate. These extracts evoked fever in rabbits and induced the release of a proinflammatory (pyrogenic) cytokine, interleukin-6 (IL-6), from human monocytic cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…16 Although it is difficult to correlate problems with medical devices with pyrogenic contamination retrospectively and the awareness for their adverse influence may not yet be very high, some reports strongly indicate a role of pyrogens in problematic medical devices, especially those made of or coated with materials of biological origin. 7,8,23 Taken together, using a model implantable material, we have shown that the IPT can be used to evaluate pyrogenic contaminations on medical devices. This assay could lead to a replacement of the rabbit pyrogen assay for this application and could improve current safety testing of biomaterials.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…16 Although it is difficult to correlate problems with medical devices with pyrogenic contamination retrospectively and the awareness for their adverse influence may not yet be very high, some reports strongly indicate a role of pyrogens in problematic medical devices, especially those made of or coated with materials of biological origin. 7,8,23 Taken together, using a model implantable material, we have shown that the IPT can be used to evaluate pyrogenic contaminations on medical devices. This assay could lead to a replacement of the rabbit pyrogen assay for this application and could improve current safety testing of biomaterials.…”
Section: Discussionmentioning
confidence: 96%
“…One prob-lem is that the rabbit may respond differently to some pyrogenic contaminations than a human. 8,9 Also, this method can only be performed with small implants. The destruction of tissue during implantation into the animal may itself cause an inflammatory reaction that does not necessarily reflect the pyrogenic contamination of the material.…”
Section: Introductionmentioning
confidence: 99%
“…), as described elsewhere [22]. Endotoxin detection was performed by Analytical Services Unit of iBET, Oeiras, Portugal using a Charles River endotoxin detection kit.…”
Section: Measurement Of Endotoxin Levelsmentioning
confidence: 99%
“…In order to facilitate the wound healing process, a range of natural biomaterials have been developed, based on cellulose, alginate, collagen and chitin, among others (Nakagawa et al, 2003). Bacterial cellulose is produced by some types of bacteria, such as Gluconacetobacter (Inder & Brown, 2012), and has been suggested for various medical applications, such as wound dressings (Czaja, Krystynowicz, Bielecki & Brown Jr, 2006;Jorfi & Foster, 2015;Petersen & Gatenholm, 2011;Portal, Clark & Levinson, 2009).…”
Section: Introductionmentioning
confidence: 99%